1991
DOI: 10.2307/3430883
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of ECG Components of Workers Exposed to Carbon Disulfide

Abstract: Thbe components of e__bvawWgmm (ECG) of 253 works exposed t carbon dulfide (CDS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…These results are in agreement with Tuchsen et al [1992] who reported increased hospitalization for ischemic heart disease was seen among workers self employed in textile industry. Kamal et al [1991] were the first to demonstrate more convincing results in ECG pathologic changes in the exposed workers. However, they were unable to relate the values of ECG components to the duration of the exposure to the chemical as well.…”
Section: Resultsmentioning
confidence: 94%
“…These results are in agreement with Tuchsen et al [1992] who reported increased hospitalization for ischemic heart disease was seen among workers self employed in textile industry. Kamal et al [1991] were the first to demonstrate more convincing results in ECG pathologic changes in the exposed workers. However, they were unable to relate the values of ECG components to the duration of the exposure to the chemical as well.…”
Section: Resultsmentioning
confidence: 94%
“…Industrial workers who are exposed to chronic low levels of carbon disulfide have a significant increased prevalence of ECG abnormalities (518)(519)(520)(521). Ventricular arrhythmias have been reported among workers with over 20 years of exposure and repolarization disturbances have been evident in workers with 10 to 20 years exposure history (522).…”
Section: Carbon Disulfidementioning
confidence: 99%
“…[10][11][12][13] Some studies showed a positive association between CS 2 exposure and outcome indices measured, while others did not. This discrepancy may be explained by differences in CS 2 exposure (intensity, duration) as well as differences in ethnic background, but a big issue to be solved is that most of the epidemiological studies in recent years were cross-sectional ones, 14 in which temporal association could not be guaranteed, and therefore it is difficult to conclude whether a causal relation exists at a relatively low concentration of CS 2 .…”
mentioning
confidence: 99%